From CRM 1.0 to CRM 2.0 and mobile CRM: a case study of European recruitment agencies - Gregório, Tânia (2015)
While companies are becoming more focused on customers and personalisation, mobile technologies and Web 2.0 have been pushing companies to evolve in this area by offering solutions to help them to approach their customers. The present research is focused on how Customer Relationship Management (CRM) systems are used, at a European level, by recruiting companies to assist candidates in finding a satisfactory job. More specifically, this paper presents a framework to identify how CRM 2.0 and mobile CRM (mCRM) can help candidates to find jobs in a personalised manner. The methodology was based on an exploratory study of European recruitment agencies, using online questionnaires. The results showed that the use of software in recruiting agencies is quite common as is the use of CRM 2.0. With concern to mCRM, their use by the agencies remains shy, leaving this channel's great potential yet to be explored.